The Current Situation of Hypertension among Rural Minimal Assurance Family Participants in Liaoning (China): A Cross-Sectional Study - Chen, Yintao (Int J Environ Res Public Health, 2016)
In China, the prevalence of hypertension is increasing and is showing an epidemic accelerating trend. However, there is a lack of studies reporting the hypertension status of rural residents with minimum living allowances. We performed a cross-sectional study including 11,435 (5285 men and 6150 women) from the general population aged ≥35 years in the Liaoning Province of China from 2012 to 2013, of which 1258 (11.0%) participants came from minimal assurance families. Anthropometric measurements, laboratory examinations and self-reported lifestyle factor information were collected by trained personnel. Multivariate logistic regression was used to detect the association between socioeconomic status (SES) and the risk of hypertension. We found that the prevalence of hypertension was as high as 61.9% in participants from minimal assurance families and the odd ratio for hypertension was 1.32 (95% CI: 1.15–1.52). The awareness, treatment, and control rates among treated hypertensive participants did not increase with higher level of income and education. In the total sample, the lower income levels increased the risk for hypertension, but education didn’t show a significant association with hypertension. Thus, there is a severe hypertension situation in the Liaoning rural population of minimal assurance families, which need more attention and prevention and control measures for hypertension.